2020
DOI: 10.3126/egn.v2i2.29237
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Sensitivity Pattern in the Mixed Intensive Care Unit in a Tertiary Care Hospital of Eastern Nepal

Abstract: Background: Empirical antibiotics are used in the intensive care unit based on developing countries’ guidelines due to a lack of a bacteriological profile of individual ICU and institution policy. Therefore, this study was conducted to know the antibiogram of the intensive care unit and to make institution policy for antibiotic use in ICU. Materials and methods: It was a prospective descriptive cross-sectional study conducted in the mixed surgical and medical intensive care unit of a tertiary care hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Our findings are similar to those of the study conducted by Keyal et al, where Klebsiella showed high rate of resistance to azithromycin (93%), amoxicillin+clavulanate(82%), and ceftriaxone (60%). 9 Staphylococcus and E coli, both were found to be resistant to Azithromycin (>80%) followed by amoxicillin+clavulante and Levofloxacin. Our study findings are similar to those seen in study done by RK Sanjana et al 8 High resistance rate to cephalosporins and quinolone antibiotics to these frequently isolated pathogens were also noted.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to those of the study conducted by Keyal et al, where Klebsiella showed high rate of resistance to azithromycin (93%), amoxicillin+clavulanate(82%), and ceftriaxone (60%). 9 Staphylococcus and E coli, both were found to be resistant to Azithromycin (>80%) followed by amoxicillin+clavulante and Levofloxacin. Our study findings are similar to those seen in study done by RK Sanjana et al 8 High resistance rate to cephalosporins and quinolone antibiotics to these frequently isolated pathogens were also noted.…”
Section: Discussionmentioning
confidence: 99%